Rethinking Gender Justice in the Quran: A Critical Exploration of Muslim Feminist Perspectives - Wijaya, Aksin; Muchlis, Ibnu; Rohmatulloh, Dawam Multazam (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
Discussions on men and women in Islam involve three major schools of thought: classical Muslim scholars, secular feminists, and Muslim feminists. While all aim to uphold women’s dignity, they diverge in their interpretations. Classical Muslim scholars emphasize justice but do not necessarily advocate absolute equality between men and women, whereas secular and Muslim feminists argue for full equality in rights and responsibilities as a form of just treatment. In particular, Muslim feminists engage in Quranic reinterpretation to uncover gender justice rooted in equality. This paper examines how Muslim feminists construct their arguments in Quranic reinterpretation, critiques the logic underlying their exegetical approach, and explores a Quranic perspective on gender justice that is both “meaningful” and contextually relevant to contemporary society. To achieve this, the study employs a critical-appreciative approach, integrating critical discourse analysis and maqasidic interpretation to analyze these three aspects. The findings highlight three key points: first, the efforts of Muslim feminists in advocating for women’s fundamental rights deserve recognition; second, their exegetical reasoning requires scrutiny, as it tends to shift from social analysis to ideological assertion; and third, the Quran presents a concept of gender justice that is dynamic and adaptable to diverse contemporary contexts. Justice in Islam does not always equate to equality; rather, it can manifest as proportional rights and responsibilities that maintain social balance and harmony. Thus, gender justice can be achieved through differentiation, provided it upholds fairness within the given context. This study bridges feminist and traditional Islamic scholarship by critically assessing Muslim feminist exegesis and proposing a contextualized framework for Quranic gender justice.